PENERAPAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN BAHASA INGGRIS (Studi Kasus di SMPN 3 Bawen) - Sri Wahyuningsih, Maria Goretti (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
Objectives of the research are to (1) determine the planning of English language learning with audiovisual media in SMP N 3 Bawen. (2) Determine the implementation of English language learning with audiovisual media in SMP N 3 Bawen. (3) Determine the evaluation of English language learning with audiovisual media in SMP N 3 Bawen. (4) Constraints that faced and how to handle it in English language learning with audiovisual media in SMP N 3 Bawen. This is qualitative research with descriptive qualitative research strategy. Methods of data collection used depth interviews, participatory observation, and documentation. Analysis of the data used the interactive model.The results showed that: (1) Planning of English learning with Audio Visual Media begins with preparing the syllabus includes learning tools, lesson plans, LCDs, Laptops and materials, which is conducted at the beginning of the semester. English teacher is sharing with other teacher, senior teachers and fellow teacher in MGMPs of English language. (2) The implementation of English learning with Audio Visual Media begins with reference to the syllabus and lesson plans; prepare teaching materials and learning software. Teacher directing students to determine learning objectives, set the lesson activity so that the material can be delivered. (3) Evaluation of learning outcomes held after completing 1 SK / KD, that performed by individuals and groups, the evaluation is in written and an oral test. the criteria of successful student with KKM value of 7.2 Point. (4) Constraints that faced are learning room is less dark so that the display on the screen is difficult to be observed. Teacherâs difficulties in the manufacturing process so that the media helped more expert teachers. The limitation ability of English teachers in preparing instructional materials, so it should look in the internet media that is not necessarily in accordance with the wishes and have spent long time. Â Keyword : Learning, Audio Visual Media, English Language